Development of Android-Based Interactive Media Using iSpring Suite 11 with the ADDIE Model for Economics Learning - Bimantoro Eko Wardhana; Dwi Herlindawati (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: This research focuses on developing Android-based interactive instructional media using iSpring Suite 11 to enhance the quality of economics learning. The study was motivated by low student engagement and suboptimal learning outcomes in Class XI-4 at SMAN Rambipuji, where a significant proportion of students did not achieve the minimum passing criteria despite the use of conventional PowerPoint media. Method: The study adopted a modified ADDIE framework, concentrating on the analysis, design, and development stages. The product was evaluated through expert appraisal to examine content and design quality, along with student-based assessments to capture perceived attractiveness. Results: The evaluation results indicate that the media achieved a content feasibility score of 97.1% and a design feasibility score of 94.2%, both categorized as highly feasible. Furthermore, the student attractiveness test yielded a score of 92.2%, indicating a very high level of attractiveness. These findings suggest that the developed media have strong potential to facilitate more engaging, interactive, and student-centered learning processes. Novelty: The novelty of this study lies in the integration of iSpring Suite 11 into Android-based interactive instructional media that are pedagogically structured and empirically validated. This study highlights the strategic role of digital instructional media as a sustainable innovation for enhancing the quality of economics education in the digital era.